2016
DOI: 10.1088/0031-8949/91/2/023005
|View full text |Cite
|
Sign up to set email alerts
|

Autorotation

Abstract: A continuous autorotation vector field along a framed space curve is defined, which describes the rotational progression of the frame. We obtain an exact integral for the length of the autorotation vector. This invokes the infinitesimal rotation vector of the frame progression and the unit vector field for the corresponding autorotation vector field. For closed curves we define an autorotation number whose integer value depends on the starting point of the curve. Upon curve deformations, the autorotation numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Nevertheless, we have shown that the geometry of the base curve is not a necessary starting point to define the shape of a rod, since the strain fields u i and v i , i = 1, 2, 3, are the only degrees of freedom needed to characterize that shape. In summary, it seems more appropriate to explicitly use rod theory when dealing with mechanical models (as exemplified by the works of Domokos [62] and Domokos & Healey [63], and many others cited above) and framed curves when focusing on geometry (as exemplified by the works of Starostin & van der Heijden [64], Bohr & Markvorsen [65], da Silva [66], and Honda & Takahashi [67]).…”
Section: Framed Curvesmentioning
confidence: 99%
“…Nevertheless, we have shown that the geometry of the base curve is not a necessary starting point to define the shape of a rod, since the strain fields u i and v i , i = 1, 2, 3, are the only degrees of freedom needed to characterize that shape. In summary, it seems more appropriate to explicitly use rod theory when dealing with mechanical models (as exemplified by the works of Domokos [62] and Domokos & Healey [63], and many others cited above) and framed curves when focusing on geometry (as exemplified by the works of Starostin & van der Heijden [64], Bohr & Markvorsen [65], da Silva [66], and Honda & Takahashi [67]).…”
Section: Framed Curvesmentioning
confidence: 99%